Post cosecha y caracterización de cacao mocambo (Theobroma bicolor Hump & Bonpl. L) y su efecto en la calidad - Zapata Quevedo , Karla Lizbeth (2023)
Cocoa Mocambo (Theobroma bicolor Hump & Bonpl. L ) Macambo Patasmuyo, pataxte, is a little known variety and very little information, is native to South America, this variety the cob is large and grooves of notorious size, its weight superior to other cocoas, the cotyledon of the almond is white hue, has a percentage Greater fat unlike other varieties of cocoa, its fermentation time is shorter unlike other varieties, its fermentation process is 72 hours, finished the fermentation process must be six days of drying in the sun to lower humidity, the present a Research was carried out at the Faculty of Industry and Production Sciences, State Technical University of Quevedo, located km 71/2, of the "La María" campus